Brazil and the South Korean experience: An Alternative Way? - Dias, Rafael (Redes. Journal of Social Studies of Science and Technology, 2008)
The set of public policies (economic, social, scientific and technological, etc.) applied in Brazil in the last two decades was strongly supported, explicitly or implicitly, by successful experiences of developed countries. However, these policies often find their source of inspiration in South Korea’s experience, an Asian country that changed from a very similar state of development to that of the Latin American countries in the decade of 1940, reaching an enviable economic and social state in a period of only fifty years. The South Korean experience has also influenced the ideas regarding possible development strategies for Brazil. The present article intends to discuss some of these ideas, linking them to the Latin-American Thought on Science, Technology and Society (PLACTS).